Qaring : A Web-Based Charity System for Orphanage Donation - BIN MOHAMMAD NOR ZAMRI, MUHAMMAD ARIF MU'AZ; Dr Firkhan (Applied Information Technology And Computer Science, 2026)
Currently, donations to orphanages are often managed manually or through fragmented platforms, leading to inefficiencies, mismatched aid, and limited donor-orphanage engagement. The main objective of this project is to develop QARING, a web-based charity system designed to streamline and manage donations to orphanages efficiently. The system enables donors to contribute monetary or item-based donations while allowing orphanages to post their needs transparently. The proposed system adopts the Waterfall model, comprising five structured phases: planning, analysis, design, implementation, and testing. Key features include user role management (Admin, Donor, Orphanage), donation tracking, orphan and needs management, and location-based matching of donors to nearby orphanages. The findings suggest that the system can enhance transparency, increase successful donation matches, and reduce the burden on orphanage staff. The structured data collected through this platform will be integrated into its modules to further improve donation efficiency and strengthen community support.